Juridical Analysis of the Rejection of Judicial Review (PK) in the Case of PT Mas Murni Indonesia, Tbk (in Bankruptcy): A Review of Supreme Court Decision No. 21 PK/Pdt.Sus-Pailit/2025 - Sheren Michi Tjandra; Claureria Angie Ely; Angelica Angelica; Udin Silalahi; Joy Zaman Felix Saragih (Transpublika Publisher, 2026)
Judicial Review is an extraordinary legal remedy designed to uphold legal certainty and justice in civil cases, including bankruptcy proceedings. This paper examines the application of Judicial Review in the bankruptcy case of PT Mas Murni Indonesia, Tbk, based on Supreme Court Decision No. 21 PK/Pdt.Sus-Pailit/2025. The study emphasizes the role of PK as a corrective mechanism against final and binding decisions, as well as the legal reasoning employed by the judges in reaching their verdict. PK in bankruptcy cases carries distinct characteristics, as it involves balancing the rights of creditors and debtors while ensuring legal certainty within the business sphere. The scope of PK is strictly limited by statutory provisions, particularly Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations (PKPU) and Law No. 48 of 2009 on Judicial Power. This research adopts a normative juridical method with statutory and case approaches, utilizing primary legal materials on bankruptcy and extraordinary remedies. Qualitative analysis reveals that despite its limited scope, PK plays a significant role in correcting misapplications of law with substantive justice implications. In the case of PT Mas Murni Indonesia, Tbk, the Supreme Court emphasized the necessity of balancing legal certainty with fairness and utility. Accordingly, this study contributes to a deeper understanding of the dynamics of Judicial Review in bankruptcy cases and illustrates how Indonesian judicial practice strives to achieve justice in line with the ultimate purpose of law.